Connections of Maghrebin and Sub-Saharan Intellectuals: Trajectories and Representations - Kedidir, Mansour (Religions, 2021)
Faced with the complex reality of their countries in the grip of multifaceted crises, the intellectuals in the Maghreb and sub-Saharan Africa are baffled. Indeed, this situation, with a wealth of lessons, ought to challenge them to reflect together on the current upheavals in their societies. Nevertheless, faced with the intricacy of current problems and their heterogeneity, these intellectuals find themselves scattered. Yet, in the past, they were bound by the same objectives. Thus, if the religious elites of the Maghreb had, during the 15th century, forged links with scholars of sub-Saharan Africa, a second wave of intellectuals succeeded them to think about the liberation of Africa and the Pan-African ideal in colonial and post-colonial contexts. However, immediately after this generation disappeared, the one that followed did not resist the disenchantment of the populations and the expansion of Arabism that influenced the formation of a generation of Maghrebin thinkers. With the bankruptcy of the socialist regimes, this hiatus heralded an era of intellectuals crumbling to the point that, with globalisation in the 21st century and the eruption of a plurality of questions, they found themselves helpless in these countries. Apart from a few attempts at building common frameworks for reflection such as those of CODESRIA or the “Esprit Panaf” pavilion at the Algiers International Book Fair, links between intellectuals from the Maghreb and sub-Saharan Africa are rare. Opposed to this type of scholars, mainly Francophone and secularised, a second type of intellectuals, rather Islamised, sharing the same representations, dominate the different spaces of the countries concerned. This paper is an attempt to explore the historical trajectory of these two types of intellectuals and then explain why, in recent decades, such a connection has marked the future of the relationship between the Maghreb and sub-Saharan Africa.